Pengaruh Pemberian Beasiswa Terhadap Hasil Belajar Mahasiswa Program Studi PPKnFKIP Universitas Riau - Widya Retno Ningsih; Gimin '; Supentri ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the effect of acceptance of the scholarship on learning outcomes among students who received scholarships in the student environment PPKn FKIP University of Riau. Formulation of the problem in this research is: